Potensi Anti Xanthomonas dari Bakteri Rizosfer Tanaman Kankung Pagar (Ipomoea carnea) - Nurmaliana Asmayani; Tri Wahyu Setyaningrum; A.A. Ngurah Nara Kusuma; Nur Indah Julisaniah; Muhammad Hari Aditia Pratama; Wanda Qoriasmadillah; Faturrahman (Master’s Program in Biology, Faculty of Mathematics and Natural Sciences, University of Mataram, 2025)
The plant pathogenic bacterium Xanthomonas campestris is a Gram-negative, rod-shaped bacterium that causes damage to plant leaves. This particular disease can result in significant economic losses and a reduction in the quality of agricultural products. An alternative method of dealing with this bacteria is to utilise the rhizosphere of kale (Ipomoea carnea) as a biological control. The objective of this study was to ascertain the antibacterial potential of the rhizosphere bacteria of kale (Ipomoea carnea) against the Xanthomonas campestris bacteria and to identify isolates with enhanced antibacterial efficacy against Xanthomonas campestris using the well diffusion method. A total of 13 bacterial isolates were obtained from the rhizosphere of kale, exhibiting distinctive round colonies, flat edges, and a white or cream colouration. A total of 12 gram-negative isolates and one gram-positive isolate were identified. The highest inhibitory activity against X. campestris was demonstrated by isolates R1, R3, and R11, with an average inhibitory zone diameter of 20.01 mm, 20.79 mm, and 20.57 mm, respectively. These values fell into the very strong inhibition category.